Repair of urethral injury associated with penile fracture using buccal mucosa graft: A novel therapeutic approach for complex cases. (December 2020) - Acimovic, Miodrag; Zivkovic, Marko; Georgescu, Alexandru Valentin; Matei, Ileana Rodica; Bumbasirevic, Uros
Highlights: Penile fracture is a rare urological emergency caused by blunt trauma to the erect penis and it may be accompanied by urethral injury. Complete urethral rupture is very uncommon and is usually managed by primary anastomosis. However, these patients are more likely to develop post-operative complications such as urethral strictures. Buccal mucosa graft is commonly used for substitution urethroplasty in management of urethral strictures, but its use has not been reported for immediate treatment in the setting of penile fracture. We report a patient with rupture of both corpora cavernosa, as well as the rupture of the urethra, after sexual intercourse. Buccal mucosa graft was used for surgical repair of urethral injury. At 36-month follow-up patient did not experience erectile or voiding problems. The application of this technique could possibly reduce the incidence of urethral strictures in these patients and further prospective studies with larger samples should be conducted. Abstract: Penile fracture is a rare urological emergency caused by blunt trauma to the erect penis and it may be accompanied by urethral injury. Complete urethral rupture is very uncommon and is usually managed by primary anastomosis. However, these patients are more likely to develop post-operative complications such as urethral strictures. Buccal mucosa graft is commonly used for substitution urethroplasty in management of urethral strictures, but its use has not been reported for immediate treatment in the setting of penile fracture. We report a patient with rupture of both corpora cavernosa, as well as the rupture of the urethra, after sexual intercourse. Buccal mucosa graft was used for surgical repair of urethral injury. At 36-month follow-up patient did not experience erectile or voiding problems. The application of this technique could possibly reduce the incidence of urethral strictures in these patients and further prospective studies with larger samples should be conducted.